Distribution of neutrons and protons in elongated targets - Zeman, Miroslav; Adam, Jindřich; Baldin, Anton Alexandrovich; Brunčiaková, Miriama; Gustov, S.A.; Katovský, Karel; Khushvaktov, Jurabek; Král, Dušan; Solnyshkin, Alexander A.; Svoboda, Josef; Šťastný, Ondřej; Tichý, Pavel; et al. (EDP Sciences, 2020)
Analysis of neutron distribution was carried out for two elongated targets. The targets have cylindrical shape and are made of lead and carbon, respectively. The dimensions are approximately one meter in length and 19 cm in diameter. The targets were irradiated with 660 MeV proton beam at Phasotron accelerator at the Joint Institute for Nuclear Research. The total number of protons was 2.35(18)E15 for the experiment with carbon target and the total number of particles at the second experiment was 2.32(19)E15. The produced neutron field was monitored by cobalt threshold activation detectors at various positions. The activation detectors were measured by means of gamma spectroscopy using HPGe detectors. Reaction rates of different radionuclides produced in the activation detectors were determined and the results from both experiments were compared. The ratios were calculated for 7 reactions produced in cobalt detectors. The ratio of the reaction rates shows that the number of residual nuclei with higher threshold energies is higher for experiment with carbon target than for the experiment with the lead target.

Analysis of neutron distribution was carried out for two elongated targets. The targets have cylindrical shape and are made of lead and carbon, respectively. The dimensions are approximately one meter in length and 19 cm in diameter. The targets were irradiated with 660 MeV proton beam at Phasotron accelerator at the Joint Institute for Nuclear Research. The total number of protons was 2.35(18)E15 for the experiment with carbon target and the total number of particles at the second experiment was 2.32(19)E15. The produced neutron field was monitored by cobalt threshold activation detectors at various positions. The activation detectors were measured by means of gamma spectroscopy using HPGe detectors. Reaction rates of different radionuclides produced in the activation detectors were determined and the results from both experiments were compared. The ratios were calculated for 7 reactions produced in cobalt detectors. The ratio of the reaction rates shows that the number of residual nuclei with higher threshold energies is higher for experiment with carbon target than for the experiment with the lead target.
Distribution of neutrons and protons in elongated targets
Keywords: ADS; transmutation; spallation; proton beam; JINR Dubna; ADS; transmutation; spallation; proton beam; JINR Dubna